Strengthening the Role of the Corruption Eradication Commission in Combating Corruption Crimes and Evaluating Its Effectiveness in Addressing Corruption Cases - Prasetyo, Anton; Herman, KMS (Devotion : Journal of Research and Community Service, 2025)
Corruption is a serious issue that hinders development in Indonesia, affecting the economy, politics, and social sectors. To address this issue, the government established the Corruption Eradication Commission (Komisi Pemberantasan Korupsi, KPK) as an independent institution tasked with the prevention, investigation, prosecution, and handling of corruption crimes. However, over time, the role and performance of the KPK have faced various challenges, including political intervention, regulatory changes, and obstacles in law enforcement. Therefore, this study aims to analyze the role and performance of the KPK in eradicating corruption crimes in Indonesia, as well as to evaluate its effectiveness in addressing corruption cases. This research uses both normative juridical and empirical methods. The normative juridical approach is carried out by analyzing various regulations related to corruption eradication, such as Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 on Corruption Eradication, as well as Law Number 19 of 2019 on amendments to the KPK Law. Additionally, this research also adopts an empirical approach by reviewing secondary data from official KPK reports and various case studies that illustrate the patterns and effectiveness of law enforcement in corruption cases in Indonesia. Through the analysis of regulations and the implementation of the KPK’s authority, this study aims to provide a more comprehensive understanding of the institution’s role in corruption eradication. The results of this research also aim to identify the challenges faced by the KPK and provide strategic recommendations to strengthen the effectiveness of the institution in carrying out its duties. Thus, this research contributes to reinforcing efforts to combat corruption in Indonesia and improving policies related to the independence and performance of the KPK.